Preservation solution Custodiol containing human alpha-1-antitrypsin improves graft recovery after prolonged cold ischemic storage in a rat model of heart transplantation - Korkmaz-Icöz, Sevil; Abulizi, Sophia; Li, Kunsheng; Korkmaz, Brice; Georgevici, Adrian-Iustin; Sayour, Alex Ali; Loganathan, Sivakkanan; Canoglu, Hansa; Karck, Matthias; Szabó, Gábor (Frontiers in Immunology, 2023)
The shortage of available donor hearts and risk of ischemia/reperfusion injury restrict heart transplantation (HTX). Alpha-1-antitrypsin (AAT), well characterized inhibitor of neutrophil serine protease, is used in augmentation therapy to treat emphysema due to severe AAT deficiency. Evidence demonstrates its additional anti-inflammatory and tissue protective effects. We hypothesized that human AAT, when added to a preservation solution, attenuates graft dysfunction after prolonged cold ischemic storage in a rat model of HTX. The hearts from isogenic Lewis donor rats were explanted, stored either for 1h or 5h in cold Custodiol supplemented with vehicle (1h ischemia, n=7 or 5h ischemia, n=7 groups) or 1 mg/ml AAT (1h ischemia+AAT, n=7 or 5h ischemia+AAT, n=9 groups), and heterotopically transplanted. Left-ventricular (LV) graft function was assessed in vivo 1.5h after HTX. Immunohistochemical detection of myeloperoxydase (MPO) was performed in myocardial tissue and expression of 88 gene quantified with PCR was analyzed both statistical and with machine-learning methods. After HTX, LV systolic function (dP/dtmax 1h ischemia+AAT 4197±256 vs 1h ischemia 3123±110; 5h ischemia+AAT 2858±154 vs 5h ischemia 1843±104 mmHg/s, p<0.05) and diastolic function (dP/dtmin 5h ischemia+AAT 1516±68 vs 5h ischemia 1095±67 mmHg/s, p<0.05) at an intraventricular volume of 90 µl were improved in the AAT groups compared with the corresponding vehicle groups. Furthermore, the rate pressure product (1h ischemia+AAT 53±4 vs 1h ischemia 26±1; 5h ischemia+AAT 37±3 vs 5h ischemia 21±1 mmHg*beats/min at an intraventricular volume of 90 µl; p<0.05) was increased in the AAT groups compared with the corresponding vehicle groups. Additionally, MPO-positive cell infiltration was significantly decreased in the 5h ischemia+AAT hearts compared to the 5h ischemia group. Our computational analysis shows that ischemia+AAT network displays higher homogeneity, higher positive and fewer negative gene correlations then the ischemia+placebo network. We provided experimental evidence that AAT protects cardiac grafts from prolonged cold ischemia during HTX in rats.